Edukasi Karakteristik Warna dengan Metode Eksperimen untuk Siswa Sekolah Dasar: Education of Color Characteristics with Methods Experimental for Elementary School Students - Utami, Dwi Rina; Seftyarizki, Debby (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Color is one of the knowledge that children must know. Therefore, since childhood, the introduction to color has been carried out, one of which is in elementary school. Until now, elementary schools that are partners tend to use the method of lecture, discussion, and memorization. Therefore, this service aims to introduce to partners the experimental method as one of the learning methods that has various advantages. The service began with group division, delivery of material about color characteristics, and conducting six kinds of experiments, namely walking water, changing color, rainbow in the plate, rainbow rain, lava lamp, and changing color with cabbage. From the service activities, it was found that students could understand the characteristics of colors correctly and were very enthusiastic about conducting experiments. In addition, the cohesiveness of students in experimenting is also intertwined. With this service activity, it is hoped that partners can make experimentation as one of the interesting classroom learning methods for students.